JUSTICE COLLABORATOR DALAM HUKUM PIDANA INDONESIA (Faculty of Law, University of Palembang, 2023)
The term justice collaborator became popular again when the alleged murder of Police Brigadier Nofriansyah Yosua Hutabarat alias Brigadier J or Brigadier Y occurred on July 8 2022 at the official residence of Inspector General of Police Ferdy Sambo. Bharada E is willing to be made a justice collaborator, and hopes that this status will be considered by the judge in the trial of the alleged murder case of Brigadier Yosua Hutabarat. This research discusses how the justice collaborator law should ideally be regulated in Indonesian criminal law. This type of research is explanatory normative legal research using secondary data with a statutory approach, case approach and concept approach. In Indonesian criminal law, justice collaborators are not specifically regulated. Therefore, it is urgent that it be regulated formally with substance: Providing protection for a justice collaborator and his family. Get a sentence of no more than 2 (two) years for serious crimes and receive a conditional sentence for ordinary crimes. Detention of suspects as justice collaborators is separated from other suspects. Given the right not to appear at the hearing. Case filings must be separated from other suspects. If the justice collaborator has become a prisoner, he will be given a special remission.